Run performance and neuromuscular control is not affected by cycling in elite international triathletes - Bonacci, J.; Saunders, P.; Alexander, M.; Blanch, P.; Chapman, A.; Vicenzino, B. (Journal of Science and Medicine in Sport, 2010)
Running is the most important discipline for success in elite Olympic distance triathlon. However, running at maximum efficiency after cycling requires the ability to limit physiological and biomechanical alterations induced by cycling. Cycling has been shown to interfere with running muscle recruitment in highly trained triathletes after a short 20 min cycle, but it is not known if this occurs in elite international triathletes or if it occurs after a cycle that simulates race conditions. Purpose: To investigate the effect of both a 20 min non-fatigue and a 50 min race-simulated cycle on running neuromuscular control and performance in elite international triathletes. Methods: Seven elite international triathletes participated. Lower limb muscle recruitment (electromyography), kinematics and running economy (sub maximal VO2) were compared between a control run (no preceding exercise) and a 30 min time trial transition run performed after two separate cycle protocols: (i) a 20 min non-fatigue cycle and (ii) a 50 min race-simulated cycle. The distance ran during the 30 min time trial transition run was also compared between the 20 min and 50 min cycles protocols. Results: Lower limb muscle recruitment, kinematics and running economy were not different between control and transition runs for either of the two cycle protocols (p > 0.05). The distance run during the 30 min transition run was also not different between the two cycle protocols (8663 ± 757 m and 8582 ± 520 m for 20 min and 50 min cycles, respectively). As opposed to previous studies on lesser performed triathletes, international elite triathletes` run performance and neuromuscular control was not adversely affected by either the non-fatigue or race-simulation cycle. Conclusion: Cycling does not adversely influence neuromuscular control or run performance in elite international triathletes. The preservation of neuromuscular control and performance during running after cycling is a unique feature of highly performing elite international triathletes and may be a reason for their success.